1991
DOI: 10.5511/plantbiotechnology1984.8.14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Macronutrients on Anthocyanin Production in Roselle (Hibiscus sabdariffa L.) Callus Cultures.

Abstract: The effects of various macronutrients on growth and anthocyanin formation in callus cultures of roselle (Hibiscus sabdaritfa L.) were investigated. Of the nutritional factors examined the type and concentration of carbon and nitrogen sources and phosphate concentration showed marked effects on the growth and anthocyanin production. Utilization of an optimized medium based on the results obtained in the present investigation resulted in a 2.5 fold increase in the anthocyanin content Potential exists for applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Increase in sucrose concentration in basal media above normally used concentrations (2-3%) has been reported to enhance production of various phenolic compounds including anthocyanin (Mizukami et al 1991) in Hibiscus sabdariffa. Those researchers clearly demonstrated that, among the different carbon sources, only sucrose and glucose were equally effective in inducing anthocyanin production, whereas fructose and maltose improved anthocyanin formation only marginally.…”
Section: Callus Inductionmentioning
confidence: 98%
“…Increase in sucrose concentration in basal media above normally used concentrations (2-3%) has been reported to enhance production of various phenolic compounds including anthocyanin (Mizukami et al 1991) in Hibiscus sabdariffa. Those researchers clearly demonstrated that, among the different carbon sources, only sucrose and glucose were equally effective in inducing anthocyanin production, whereas fructose and maltose improved anthocyanin formation only marginally.…”
Section: Callus Inductionmentioning
confidence: 98%
“…Abiotic stresses that induce anthocyanin synthesis include drought in rice and Arabidopsis (Basu et al 2010 ; Sperdouli and Moustakas 2012 ), cold in maize, Arabidopsis , and citrus (Christie et al 1994 ; Crifò et al 2011 ), high salt in tomato and red cabbage (Eryılmaz 2006 ), nutrient deficiency in Arabidopsis , hibiscus, and carrot (Mizukami et al 1991 ; Rajendran et al 1992 ; Jiang et al 2007 ), osmotic stress in carrot callus and grapevine cell cultures (Rajendran et al 1992 ; Suzuki 1995 ), and exposure to low pH of the medium in strawberry suspension cell cultures (Zhang and Furusaki 1997 ; reviewed by Chalker-Scott 1999 ; Winkel-Shirley 2002 ). The presence of sucrose in the culture medium also induces anthocyanin synthesis by a mechanism dependent on the MYB transcription factor, PAP1 (Teng et al 2005 ; Solfanelli et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bazı çalışmalara göre diğer şekerlerle karşılaştırıldığında fruktoz içeren ortam, en etkili olan ortam olmuştur. Aralia cordata L. (Sakamoto, 1993), Hibiscus sabdariffa L. (Mizukami, 1991) ve Fragaria vesca L. (çilek) kallus kültürlerinde antosiyanin birikimine neden olmuştur (Mori ve Sakurai, 1994). Laktoz ise mutant bir havuç hücre hattında antosiyanin üretimini artırmıştır (Nagarajan, 1989), Daucus carota L.' nın kallus kültürlerinde sükroza mannitol takviye edildiğinde antosiyanin miktarında önemli artış olmuştur (Rajendran ve ark., 1992).…”
Section: Antosiyaninlerin İn Vitro üRetimiunclassified